Fundraising for Special Olympics on college campuses: guidelines for campus-level fundraising - Kipper, Eric, author (Colorado State University. Libraries, 2024)
Several studies have reported on general fundraising techniques; This research paper attempts to find the best way to fundraise for Special Olympics on a college campus. Research was done by analyzing academic sources and organizing interviews with leaders of collegiate Special Olympics programs (Unified Colleges) from around the nation. Based off this research, I suggest that planned events, social media, social networks, and university athletics are all important aspects of a successful fundraiser. The fundraiser that I executed at Colorado State University (CSU) indicates that my research was accurate. The fundraiser described in this paper raised over $300 for CSU Special Olympics and supports that an effective way to fundraise for Special Olympics on a college campus is to create an event-driven fundraiser that takes advantage of social networks, social media, and the university’s athletic department.
HONR 499: Senior Honors Thesis.